Evaluation of gellan gum-glufosinate ammonium beads and its release study performance - Azahari, Nurul Atiqah; Mohamad Jaafar, Adila; Rayung, Marwah; Asib, Norhayu; Mamat, Mazidah (Malaysian Institute of Chemistry, 2023)
The aim of this study is to prepare hydrogel beads that contain the herbicide of glufosinate ammonium (GA). Gellan gum (GG) is used as a host material, due to its interesting properties which are biodegradable and biocompatible. Hydrogel having the hydrophilic structure of which renders them capable of holding large amounts of water in their three-dimensional networks. GA is a type of contact herbicide that is used to control weeds and unwanted plants in agriculture industry. GA acts as a guest species to be incorporated into host, GG to produce controlled release formulation of herbicide. GG beads were prepared by ionotropic gelation using calcium chloride solution as a crosslinker. In the preparation of GG hydrogel beads loaded with GA, different concentrations of GA which are 0.4 M, 0.8 M, 1.2 M and 1.6 M were prepared. From the results obtained, FTIR spectrum showed the combination of both functional groups from the host and guest species even when different concentrations of GA were used. Elemental analysis of CHNS showed that the GG loaded with GA have an increase in the carbon, hydrogen, nitrogen and sulfur contents which is due to the successful incorporation of various concentrations of GA into the GG. From the TGA-DTG thermogram, thermal stability showed that the weight loss was influenced by the concentrations of the incorporated GA. The release profile of the GA from the gellan gum beads showed the release of GA completed on the sixth day.